Lumbar Epidural: Anatomical and Clinical Study in Dogs Submitted to Ovariohysterectomy - Cima, Daniela Santilli; Credie, Leonardo de Freitas Guimarães Arcoverde; Futema, Fábio; Luna, Stelio Pacca Loureiro (Frontiers in Veterinary Science, 2020)
Epidural anesthesia minimizes perioperative pain in dogs. It is considered that epidural solution dispersion in cadavers is similar to alive dogs. The objective of the anatomical study was to compare the dispersion of 0.2 mL/kg 0.25% bupivacaine and iohexol via lumbar epidural (L1-L2) under fluoroscopic guidance in 10 thawed cadavers (GC) and 13 female dogs (G0.25) (5-15 kg; body score 4/5). The objective of the clinical study was to evaluate postoperative analgesic consumption and sedation for 6 hours after extubation of dogs submitted to ovariohysterectomy when using 0.25% (G0.25; n=10) bupivacaine with the intraoperative use of fentanyl (GF; n=10). Parametric data were compared by the t-test and non-parametric data by the Mann Whitney test. Pain and sedation scores were evaluated over time by the Friedman test, followed by the Dunn test. Alive dogs presented greater epidural dispersion (17 ± 3 vertebrae) than thawed cadavers (11 ± 4 vertebrae; p=0.002). All dogs treated with fentanyl and only one dog treated with 0.25% epidural bupivacaine presented pain scores above the cut-off point of the Glasgow Composite Measure Pain Scale Short-Form (GCMPS-SF) and required postoperative rescue analgesia up to 6 hours after extubation. The sedation score was higher at all postoperative moments compared to preoperative moments in the G0.25 and GF, except for evaluations performed at 5 and 6 hours after extubation in the GF. Greater sedation was observed immediately after extubation in the GF compared to the G0.25, and there was greater sedation in the G0.25 compared to the GF from 3 to 6 hours after extubation. The conclusion of the anatomical study was that L1-L2 epidural bupivacaine dispersion is lower in canine thawed cadavers than in alive dogs. Conclusion of the clinical study was that lumbar epidural anesthesia improved postoperative analgesia and produced longer postoperative sedation when compared to fentanyl.